2007
DOI: 10.1542/peds.2006-2630
|View full text |Cite
|
Sign up to set email alerts
|

Dose Response and Efficacy of a Live, Attenuated Human Rotavirus Vaccine in Mexican Infants

Abstract: This new oral, live, attenuated human rotavirus vaccine was safe, immunogenic, and highly efficacious in preventing any and, more importantly, severe rotavirus gastroenteritis in healthy infants. This vaccine produced comparable protection to natural infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 21 publications
1
33
0
1
Order By: Relevance
“…RV1 vaccinederived virus has a lower ID 50 (∼10 5 PFU/mL or less) that may present a higher chance of viral transmission. 17 Transmission of rotavirus vaccine strain RV1 to unvaccinated individuals has been assessed in many studies [18][19][20][21][22][23][24][25] but only documented as occurring in 3. [18][19][20] In studies documenting RV1 transmission, seroconversion varied from 2% to 6% among placebo recipients.…”
Section: Discussionmentioning
confidence: 99%
“…RV1 vaccinederived virus has a lower ID 50 (∼10 5 PFU/mL or less) that may present a higher chance of viral transmission. 17 Transmission of rotavirus vaccine strain RV1 to unvaccinated individuals has been assessed in many studies [18][19][20][21][22][23][24][25] but only documented as occurring in 3. [18][19][20] In studies documenting RV1 transmission, seroconversion varied from 2% to 6% among placebo recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response to live oral rotavirus vaccines differs between infants in developed and developing countries. The immune seroconversion response observed in the previous rotavirus vaccine study in South Africa was lower than that seen in studies in Latin America [10][11][12]. In addition, early rotavirus vaccine trials in Africa, with alternative rotavirus vaccine candidates, demonstrated poor or no efficacy [13][14][15].…”
mentioning
confidence: 99%
“…22 RV1 also is frequently shed by immunized children (approximately 50%-80%), mainly during the 7 days following the first dose; and transmission to contacts has been documented. [23][24][25] A unique study of 100 twin pairs in Dominican Republic estimated that the risk of household transmission of RV1 to the unimmunized twin (all asymptomatic cases) was 19%. 26 In contrast, shedding of RV5 has been detected at different frequencies (9% and 21% in healthy infants 27,28 and 55% in premature infants 29 ), and even though transmission to unimmunized children has been documented, it seems to occur only occasionally.…”
Section: What Could Be the Mechanism(s) Of Herd Immunity?mentioning
confidence: 99%